Social change - Moore, Wilbert E. (New Delhi, 2004)
This compact text outlines and evaluates comparative theories of social change in a direct and unpretentious format. An enormous number of research studies, primarily descriptive in nature, reflect some fundamentals changes in sociology and have produced a wealth of new material for study. The author proceeds to incorporate the most promising of these ideas and insights in his desire to keep the presentation compact and critical. Two new sections-on inequality and the revision of functional notions-have been added to update this enlivening and somewhat unorthodox analysis of the conflict between change and order.
Keywords: Social change